Avaliação da pesquisa de cristais de CHARCOT-LEYDEN nas fezes, como método de diagnóstico laboratorial auxiliar de infecções parasitárias intestinais - Sá, Maria de Fátima Leal Manhães de (2007)
The aim of this work is to evaluate the presence of Charcot-Leyden crystals in stool specimens as an auxiliary reliable laboratorial diagnostic method and to establish a methodological protocol of parasitological exam of feces to determine the presence of enteroparasitosis. Stool and blood samples of two distinct populations were analyzed in order to determine the prevalence. The first group was composed of 168 children (of both sexes and between 2 and 5 years and 11 months old) who are enrolled in public daycare centers in Niterói, in the state of Rio de Janeiro. The second group was composed of 369 patients from the Antônio Pedro University hospital (HUAP). All exams from both groups were analyzed in the same period, in the Hematology and Parasitology Laboratories of HUAP. The stool specimens from the children were collected in labeled plastic vials with 10% buffered formaldehyde and processed through the standard Coprotest method. Specific white cell count was determined from the blood that was collected by finger prick with appropriate lancet. The blood smear was prepared immediately, stained with Wright stain and subsequently analyzed under a optic microscope with a 1000 fold magnification. The counts were undertaken with the help of a differential cell counter. The blood samples of the outpatients from HUAP were processed in the hospitals Hematology Laboratory, in an automatic cell counter. The parasitological exams of the stool specimens of both outpatients and children were processed by routine methods used in HUAP s Parasitology Laboratory. In short, smears were prepared as of the stool samples and stained subsequently with Wright stain to search for the presence of Charcot-Leyden Crystals. The stool smears were analyzed under an optic microscope with a 1000 fold increase to determine the presence of enteroparasitosis and Charcot-Leyden Crystals. The presence of eosinophils in the blood smears was searched to establish a possible correlation between the findings in the studied populations. The most frequent intestinal parasites encountered in the daycare center population were: Blastocystis hominis (20%), Entamoeba coli (10%), Giardia lambia (8%) while in HUAP´s outpatient population were: Entamoeba coli (15%), Giardia lambia (11%), Strongyloides stercoralis (6%) and Blastocystis hominis (5%). The presence of Charcot-Leyden Crystals showed to be a quick, low cost and highly efficient method in the aid of parasitological exam in stool specimens, when associated to the presence of eosinophilia in the peripheral blood. The detection of these pathogenic enteroparasites suggests poor hygiene conditions of the studied populations